Feeling for the Other With Ease: Prospective Actors Show High Levels of Emotion Recognition and Report Above Average Empathic Concern, but Do Not Experience Strong Distress - Schmidt, Isabell; Rutanen, Tuomas; Luciani, Roberto S.; Jola, Corinne (Frontiers in Psychology, 2021)
Differences in empathic abilities between acting, dance, and psychology students were explored, in addition to the appropriateness of existing empathy measures in the context of these cohorts. Students (N=176) across Higher Education Institutions in the UK and Europe were included in the online survey analysis, consisting of the Reading the Mind in the Eyes (RME) test, the Interpersonal Reactivity Index (IRI), the Empathy Quotient (EQ), and the E-drawing test (EDT), each measuring particular facets of empathy. Based on existing evidence and our understanding of the discipline practices, we predicted that acting students would perform the best at identifying people’s emotional expressions but might lack other empathy skills, such as emotional concern. This cohort thus provides an opportunity to evaluate different empathy measures. While actors showed significantly higher RME scores than dancers, the difference between actors and psychologists was marginal. Moreover, actors’ scores did not differ significantly on other empathy measures, such as their concern for others’ emotional wellbeing or fantasy, both measured by IRI subscales. Psychology students scored highest in the IRI perspective taking subscale and the data supported anecdotal evidence that psychologists were more concerned for others’ emotional wellbeing than dancers or actors. Dancers seemed the least concerned with others’ perspectives and emotional states, which we explained through a somatosensory ‘inward’ focus required by their art form. Nevertheless, compared to the general population, our groups reported higher empathic abilities on all IRI subscales except for personal distress. Altogether, our study shows that the RME, the IRI, and the EDT vary in their susceptibility to different facets of empathic abilities in acting, dance, and psychology students whereas the EQ does not. Emotions can for example be expressed and perceived through language, facial expressions, or behaviour. As many empathy tests focus on one type of signal they might thus miss other strategies. Where empathy tests are applied to individuals that have a predominance to read or respond to others in a particular way, as we showed through these three disciplines, they might not capture these. We thus propose that empathy tests must evolve by means of integrating varied forms of communication.